The evolving landscape of imprinted genes in humans and mice: Conflict among alleles, genes, tissues, and kin. (18th March 2016) - Wilkins, Jon F.; Úbeda, Francisco; Van Cleve, Jeremy
Abstract : Three recent genome‐wide studies in mice and humans have produced the most definitive map to date of genomic imprinting (gene expression that depends on parental origin) by incorporating multiple tissue types and developmental stages. Here, we explore the results of these studies in light of the kinship theory of genomic imprinting, which predicts that imprinting evolves due to differential genetic relatedness between maternal and paternal relatives. The studies produce a list of imprinted genes with around 120–180 in mice and ∼100 in humans. The studies agree on broad patterns across mice and humans including the complex patterns of imprinted expression at loci like Igf2 and Grb10 . We discuss how the kinship theory provides a powerful framework for hypotheses that can explain these patterns. Finally, since imprinting is rare in the genome despite predictions from the kinship theory that it might be common, we discuss evolutionary factors that could favor biallelic expression. Abstract : We explore three recent genome‐wide studies of genomic imprinting (gene expression dependent on parental origin) in light of the kinship theory for genomic imprinting. These studies leverage multiple tissues and developmental stages in mice and humans to produce the most definitive map of genomic imprinting to date.